1994
DOI: 10.1111/j.1398-9995.1994.tb02098.x
|View full text |Cite
|
Sign up to set email alerts
|

The profiles of interleukin (IL)‐2, IL‐6, and interferon‐gamma production by peripheral blood mononuclear cells from house‐dust‐mite‐allergic patients: a role for IL‐6 in allergic disease

Abstract: We have developed a model to measure cytokine production by peripheral blood mononuclear cells (PBMC) in vitro. In this report, we examine the production of interleukin-2 (IL-2), IL-6, and interferon-gamma (IFN-gamma) by PBMC of house-dust-mite (Dermatophagoides pteronyssinus)-allergic subjects. When stimulated with specific allergen (D. pteronyssinus), PBMC of patients produced significant levels of IL-2 and high levels of IL-6, but little or no IFN-gamma. Nonatopic control PBMC also produced IL-6, although a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
3
18
1
Order By: Relevance
“…The possibility that Th2-type cytokines instead play a part in the pathogenesis of ACD, as is the case in atopic allergies [28][29][30], is not always considered. However, despite the correlations observed between patch test reactivity and cytokines representing both Th1-type and Th2- .................................................................................................................................................................................................... [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that Th2-type cytokines instead play a part in the pathogenesis of ACD, as is the case in atopic allergies [28][29][30], is not always considered. However, despite the correlations observed between patch test reactivity and cytokines representing both Th1-type and Th2- .................................................................................................................................................................................................... [19].…”
Section: Discussionmentioning
confidence: 99%
“…Although no consideration with regard to the atopic status of the subjects was taken when including subjects in the study, their IgE plasma levels were measured, because it is a blunt but nevertheless relevant correlate for the atopic status [29,30]. It is reasonable to expect a possible influence of the atopic status on the response to contact allergens, because atopic conditions can modulate responses to nonallergen antigens towards Th2-type [28,31]. Also, it was recently shown that Ni 2þ contact allergic subjects with concomitant atopic dermatitis responded to Ni 2þ with lower proliferative as well as IL-2 in vitro responses in comparison with Ni 2þ -allergic subjects free of atopic dermatitis symptoms [32].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 and IL-8 are known to stimulate proliferation of cultured human keratinocytes [19, 20]and IL-8 causes skin inflammation characterized by neutrophilic and lymphocytic infiltration [20]. Increased numbers of IL-8-producing cells are found in the dermis of atopic patients [21], and PBMC from patients with AD produced significantly higher levels of IL-6 and IL-8 compared to healthy nonatopic controls [8, 9]. McHugh et al [8]showed that early and sustained production of large amounts of IL-6 typifies the immune response to specific allergens in atopic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Altered cytokine and chemokine production by T cells and monocytes/macrophages is a key step in the induction of inflammatory skin reactions in AD [3, 4, 8, 9, 10]. IL-6 and IL-8 are known to stimulate proliferation of cultured human keratinocytes [19, 20]and IL-8 causes skin inflammation characterized by neutrophilic and lymphocytic infiltration [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation